Sheikh Ma'ruf al-Nudhi's efforts in the science of Hadith - Ahmad, L.Dr.Asoo Reza (Sulaimani Journal for Humanities, 2024)
Sheikh al-Nawdahi was one of the most distinguished Kurdish scholars, leaving a significant mark on the fields of teaching and writing. He taught hundreds of students in his time across various disciplines, including jurisprudence, theology, hadith, grammar, rhetoric, and the principles of jurisprudence. His brilliance was evident in his composition of most of his works in the form of poems and verses, a style unmatched by his contemporaries. A number of scholars have written commentaries on his poems and writings, recognizing their immense benefit to students and teachers alike. This research focuses on Sheikh Ma'ruf al-Nawdahi's contributions to hadith studies in his poems. The researcher diligently collected material related to hadith studies from these poems, employing an inductive-analytical approach. The aim was to highlight his contributions to hadith studies and demonstrate his profound expertise in this field. He excelled in his versification of the book "Nuzhat al-Nazar," adding to the discussion of issues not mentioned by the original author and clarifying ambiguities in others. In his other poems, his emphasis on citing Prophetic hadiths as a foundation for his arguments is evident. Then I concluded with the main findings and recommendations.
Keywords: Service; Kurdish scholars; Nodhi; Hadith science; inductive